Internal Audit Coso Framework Pada Fungsi Keuangan Berbasis Digital Untuk Menilai Kinerja Keuangan Di CV. Inti Bumi Multigrup - Debby Yusriliana Rahmawati; Tri Ratnawati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This research aims to determine how the role of digitalization on internal control How digitalization is used to assess the effectiveness of internal control in the financial function, how digitalization can make financial performance more efficient. This research is a descriptive qualitative research that measures and describes a certain social phenomenon by collecting facts, but without testing hypotheses using a triangulation approach, namely documentation, observation, and interviews. 1. The financial system still does not use digitization or is still manual 2. Competency mismatches can affect the results of the company's financial statements 3. Not confirming to suppliers or to their customers 4. Mixing company accounts with personal accounts. Based on the results of the discussion, it can be seen that the number and competence of human resources is very important, so internal control over the financial function at CV. Inti Bumi Multigrup is very necessary. Based on the COSO Framework, it can be concluded that internal control in CV. Inti Bumi Multigrup is not good enough, where: 1. The financial system still does not use digitization or is still manual 2. Competency mismatches can affect the results of the company's financial statements 3. Not confirming to suppliers or to their customers 4. Mixing company accounts with personal accounts The author's research suggestion for CV. Inti Bumi Multigrup is that it can pay more attention to the conditions of the financial and administrative sections or financial functions so that they are in accordance with applicable accounting standards and can also make it easier to analyze data for decision making.